Experimental and numerical investigation of crack growth behavior in a dissimilar welded joint. (October 2020) - Alves, Daniel N.L.; Almeida, José G.; Rodrigues, Marcelo C.
Highlights: Crack growth on dissimilar welded joint (DWJ) follows a preferential plastic strain flow. Stress fields at the crack tip and DWJ constraints determine strain fields deviation. The triaxiality at the crack tip is responsible for penetration (point-to-point) into the material body. Abstract: Structural efficiency in mechanical systems has strongly targeted economic optimization and structural safety. Understanding the response of materials under adverse conditions is essential for designing a safe project. Oil and natural gas industry in deep waters has been facing enormous scientific and technological challenges. Dissimilar welds application on these industries is extensive and routine. After many years of successful service, a series of catastrophic failures have recently been reported during service [Burk; Ribardo, 2010; Haldorsen; Dodge, 2017], in special the AISI 8630 - alloy 625 combination. These facts have signalized a root lack of understanding of these failures that occurred around the dissimilar welded joint fusion line. Although numerous articles have been published in recently, mechanisms of this phenomena are not yet well defined. This work, whose central motivation emerges from the need to provide information about mechanisms of the crack tip behavior in order to mitigate technical engineering problems arising from deep-water exploration, it aimed to investigate the growth of cracks (from the perspective of fracture mechanics) located in a dissimilar welded joint (DWJ) frequently used (ASTM A-36, Inconel 625 and AISI 8630M) to join pipes in offshore oil production lines. The crack was placed 1 mm away from the fusion line of Inconel-AISI 8630M towards the AISI 8630M. The finite element method (FEM) was used to better understand the experimental results through analysis of the stress and strain fields generated during specimen loading. The FEM-based numerical analysis enabled observation of the critical stress area and the preferential plastic flow in the DWJ specimen, which the literature claims is an indicator of the crack growth path. The results obtained through the numerical analysis showed a convergent behavior in relation to the plastic flow, which was qualitatively and quantitatively in agreement with the experimental test results.